Nesting habits of the bluethroat Luscinia svecica at Kilpisjärvi, Finnish Lapland (Sinirinnan pesinnästä Kilpisjärvellä). - Järvinen, Antero; Pryl, Mikko; Tast, Johan; Kaikusalo, Asko (Kilpisjärven biologinen asema, 2018)
Järvinen, A. & Pryl, M. Nesting habits of the bluethroat Luscinia svecica at Kilpisjärvi, Finnish Lapland (Sinirinnan pesinnästä Kilpisjärvellä). Tast, J. Breeding season and litter size of the field vole Microtus agrestis at Kilpisjärvi, Finnish Lapland (Peltomyyrän Microtus agrestis lisääntymiskausi ja poikuekoko Kilpisjärvellä). Kaikusalo, A. Kilpisjärven seudun päästäiset (The shrews of the Kilpisjärvi area, Finnish Lapland).